Magnesium hydroxide reinforced kenaf fibers/epoxy hybrid composites: mechanical and thermomechanical properties - Saba, Naheed; Alothman, Othman Y.; Almutairi, Z.; Jawaid, Mohammad (Elsevier, 2019)
The present article deals with the fabrication of magnesium hydroxide (MH) filler reinforced kenaf/epoxy hybrid composites with different loading (10%, 15%, 20% and 25% by wt). Tensile, impact, flexural, morphological, thermal stability and dynamic mechanical properties of the developed MH/kenaf/epoxy hybrid composites were evaluated and compared. The analysis of the results revealed that the incorporation of the stiff MH particles into the kenaf/epoxy composites enhanced their tensile, flexural and impact properties, as well as their residual content. Enhancement in both storage (E′) and loss (E″) moduli, as well as a considerable decrease in damping factor (Tan δ), was observed in the hybrid composites, compared to the kenaf/epoxy composites. Moreover, a remarkable improvement in properties was noticed for the 20% MH hybrid composites, which was ascribed to better dispersion and interfacial interaction between the kenaf fibers and the epoxy within composites, enabling more efficient interfacial stress transfer. Overall, the 20% MH/kenaf/epoxy hybrid composites presented better mechanical strength, thermal stability and dynamic properties compared to the rest of the hybrid composites developed in this study.